Introduction of a hexavalent vaccine containing acellular pertussis into the national immunization program for infants in Peru: a cost-consequence analysis of vaccination coverage - Janice Seinfeld; Alfredo Sobrevilla; María Laura Rosales; Mauricio Ibañez; César Munayco; Delia Ruiz (BMC, 2024)
Abstract Background Infant vaccination coverage rates in Peru have declined in recent years, exacerbated by the COVID-19 pandemic. Introduction of the fully-liquid diphtheria, tetanus, and acellular pertussis (DTaP)-inactivated polio vaccine (IPV)-hepatitis B (HB)-Haemophilus influenzae type B (Hib) hexavalent vaccine (DTaP-IPV-HB-Hib) in Peru's infant National Immunization Program may help improve coverage. We evaluated costs and healthcare outcomes, including coverage, of switching from a pentavalent vaccine containing whole-cell pertussis component (DTwP-HB-Hib) plus IPV/oral polio vaccine (IPV/OPV) to the hexavalent vaccine for the primary vaccination scheme (2, 4 and 6 months). Methods The analysis was performed over a 5-year period on a cohort of children born in Peru in 2020 (N = 494,595). Four scenarios were considered: the pentavalent plus IPV/OPV scheme (S1); replacing the pentavalent plus IPV/OPV scheme with the hexavalent scheme (S2); expanded delivery of the pentavalent plus IPV/OPV scheme (S3); expanded delivery of the hexavalent scheme (S4). Vaccine coverage and incidence of adverse reactions (ARs) were estimated using Monte Carlo simulations and previous estimates from the literature. Cases of vaccine-preventable diseases were estimated using a Markov model. Logistical and healthcare costs associated with these outcomes were estimated. Impact of key variables (including coverage rates, incidence of ARs and vaccine prices) on costs was evaluated in sensitivity analyses. Results The overall cost from a public health payer perspective associated with the pentavalent plus IPV/OPV vaccine scheme (S1) was estimated at $56,719,350, increasing to $61,324,263 (+ 8.1%), $59,121,545 (+ 4.2%) and $64,872,734 (+ 14.4%) in scenarios S2, S3 and S4, respectively. Compared with the status quo (S1), coverage rates were estimated to increase by 3.1% points with expanded delivery alone, and by 9.4 and 14.3% points, if the hexavalent vaccine is deployed (S2 and S4, respectively). In both scenarios with the hexavalent vaccine (S2 and S4), pertussis cases would also be 5.7% and 8.7% lower, and AR rates would decrease by 32%. The cost per protected child would be reduced when the hexavalent vaccine scheme. Incidence of ARs was an important driver of cost variability in the sensitivity analysis. Conclusions Implementation of the hexavalent vaccine in Peru's National Immunization Program has a positive public health cost consequence.